(untitled) (Swiss Medical Weekly, 2019)
This update on plasma cell myeloma has been elaborated by a Swiss expert panel as a result of the plethora of new data on the treatment of plasma cell myeloma reported recently. It adds new insights to the more extensive review that was published 3 years ago and may help clinicians on decision making for their patients. The new recommendations for distinguishing plasma cell myeloma from smouldering myeloma are briefly presented, including a section on contemporary imaging studies with this respect. Former panel recommendations that remain unchanged by new results will not be discussed in detail as the major focus of this review is on treatment-relevant new developments.